Effect of inoculation with Acaulospora and Glomus on the growth and nutrition of blueberries (Vaccinium corymbosum) with different fertilization levels - Roveda-Hoyos, Gabriel; Venegas-Gómez, Julián Felipe; Moreno-Fonseca, Liz Patricia; Magnitskiy, Stanislav; Ramírez-Gómez, Margarita (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
In recent years, the global demand for blueberries has been growing because of its nutraceutical properties in the fruits, which provide important benefits to human health. Colombia, thanks to its diversity, has a great opportunity to meet the blueberry demands of the global markets. In the present study, the effect of two arbuscular mycorrhizal fungi (AMF) of the genera Glomus and Acaulospora were evaluated on the growth of blueberry plants var. Biloxi, subjected to three levels of chemical fertilization (100, 50 and 0%), with the 100% level being optimal. The blueberry plants inoculated with Glomus under conditions of nutrient deficiency (50AMF1+) increased dry mass, height, number of basal branches, leaf area, root/shoot ratio, and chlorophyll concentration, which were significantly higher than in the plants without inoculation with nutrient deficiency (0AMF- and 50AMF-). The plants inoculated with Glomus achieved an increase in height, while the plants inoculated with Acaulospora increased the number of basal branches when grown under a nutrient deficiency (50AMF+1) in relation to the uninoculated controls (0AMF- and 50AMF-). The results suggested that the best association of blueberry occurs with Glomus, with increased plant growth and nutrition (N, P, K, Ca, Mg, and S).